2003
DOI: 10.1046/j.1365-313x.2003.01809.x
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic tobacco plants expressing antisense ferredoxin‐NADP(H) reductase transcripts display increased susceptibility to photo‐oxidative damage

Abstract: SummaryFerredoxin-NADP(H) reductase (FNR) catalyses the ®nal step of the photosynthetic electron transport in chloroplasts. Using an antisense RNA strategy to reduce expression of this¯avoenzyme in transgenic tobacco plants, it has been demonstrated that FNR mediates a rate-limiting step of photosynthesis under both limiting and saturating light conditions. Here, we show that these FNR-de®cient plants are abnormally prone to photo-oxidative injury. When grown under autotrophic conditions for 3 weeks, specimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
43
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 34 publications
8
43
0
Order By: Relevance
“…In tobacco (Nicotiana tabacum), a pathogeninduced mitogen-activated protein kinase cascade disrupts chloroplast metabolism and leads to a rapid shutdown of CO 2 fixation, a phenomenon that is expected to favor light-dependent excess excitation energy conditions in thylakoids and ROS production (Liu et al, 2007). It is also worth mentioning that compromised linear electron transport in transgenic tobacco plants with reduced ferredoxin-NADP(H) reductase levels also led to increased generation of 1 O 2 , eventually followed by cell death (Palatnik et al, 2003). Apparently, environmental stresses that initiate cell death programs converge at halted chloroplast metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In tobacco (Nicotiana tabacum), a pathogeninduced mitogen-activated protein kinase cascade disrupts chloroplast metabolism and leads to a rapid shutdown of CO 2 fixation, a phenomenon that is expected to favor light-dependent excess excitation energy conditions in thylakoids and ROS production (Liu et al, 2007). It is also worth mentioning that compromised linear electron transport in transgenic tobacco plants with reduced ferredoxin-NADP(H) reductase levels also led to increased generation of 1 O 2 , eventually followed by cell death (Palatnik et al, 2003). Apparently, environmental stresses that initiate cell death programs converge at halted chloroplast metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Plants Accumulating FNR Display Increased Tolerance to Photooxidative Damage and Redox-Cycling Herbicides FNR-deficient plants were highly sensitive to photoinactivation, undergoing leaf bleaching, lipid peroxidation, and membrane damage even under moderate irradiation (Palatnik et al, 2003). The magnitude of the effect was directly dependent on the light intensity and the extent of FNR depletion.…”
Section: Effects Of Fnr Overexpression On Plant Growth and Photosynthmentioning
confidence: 99%
“…Plants containing 20% to 70% of the reductase present in nontransformed siblings displayed growth arrest, chlorophyll (chl) degradation, and impaired CO 2 uptake. They were also abnormally prone to photooxidative damage (Palatnik et al, 2003). Control analysis revealed that FNR mediates a rate-limiting step of photosynthesis under both limiting and saturating light conditions (Hajirezaei et al, 2002), raising the possibility that overexpression of this flavoprotein could stimulate photosynthesis and ultimately lead to increased biomass production.…”
mentioning
confidence: 99%
“…Furthermore, tobacco (Nicotiana tabacum) plants deficient in ferredoxin-NADP(H) reductase exhibit a yellow-green phenotype due to the overreduction of the intersystem PET chain. The extent of this phenotype is directly dependent upon the irradiance to which the plants are exposed (Palatnik et al, 2003). Consequently, it has been suggested that the chloroplast has a dual role.…”
Section: Introductionmentioning
confidence: 99%